Analysis of Indonesian Social Security Administrator Policy Implementation in Improving Service Quality - Zahrah Fadhillah Nasution; Chrismis Novalinda Ginting; Muhammad Faridz Syahrian (Newinera Publisher, 2025)
This study analyzes the implementation of the National Health Insurance (JKN) policy administered by the Badan Penyelenggara Jaminan Sosial in enhancing service quality at Royal Prima Marelan General Hospital. The primary issues identified include insufficient dissemination of policy guidelines to medical personnel and patients, complex administrative procedures, and limited service facilities available to JKN participants. Using a descriptive-analytic approach, the research applies the SERVQUAL (Service Quality) model and the Expectancy–Disconfirmation Theory (EDT) to evaluate the gap between patient expectations and perceived service quality. Data were obtained through observations, interviews, and questionnaires involving medical staff, administrative officers, and JKN patient participants. The findings reveal that the Tangibles and Reliability dimensions are relatively satisfactory; however, Responsiveness and Empathy remain low due to limited human resources and heavy workloads. The implementation of JKN policies by the Badan Penyelenggara Jaminan Sosial has not been fully optimized, primarily due to inadequate training, the absence of integrated digital information systems, and limited managerial support for systematic service quality monitoring and evaluation. Based on the EDT assessment, a notable mismatch exists between patient expectations and actual service experiences, resulting in dissatisfaction. Integrating the JKN policy framework with SERVQUAL and EDT highlights the need to strengthen policy dissemination, enhance human resource capacity, and reform management systems through digitalization and a human-centered approach to ensure equitable, efficient, and sustainable health services at Royal Prima Marelan General Hospital.